Comparison between China, the EU and the US's climate and energy governance: How policies are made and implemented at different levels - Xinqing Lu; Erpu Zhu; Loyle Campbell; Manfred Hafner; Michel Noussan; Pier Paolo Raimondi (Fondazione Eni Enrico Mattei (FEEM), 2021)
This paper compares the different multi-level climate and energy governance in China, the European Union and the United States. While many comparisons across these three economies exist, they concentrate on comparing the climate and energy “policy instruments” and their results. This paper puts a focus on the importance of institutionalized multi-level governance processes, i.e., the “politics” - the actors and interaction processes inherent in a mode of governance, and the “polities” - the institutional setting. How are priorities and targets decided from both bottom-up and top-down processes? How do the central governments exert control over local authorities and ensure the implementation of their policies? How do the central governments enforce and evaluate the results of the policies? And finally, how do citizens play a role in the multi-level governance in these three blocs? Analysis of multilevel governance highlights the importance of target setting and cadre evaluation in China whereas legislation is the dominant process in the EU and the US.
Keywords: N50; Q48; Q58; 330; Multi-level Governance; Climate Policy; Energy Policy; Energy Transition; China; the European Union; the United States